Development of a stable liquid formulation of live attenuated influenza vaccine. Issue 32 (12th July 2016) - White, Jessica A.; Estrada, Marcus; Flood, E. Alexander; Mahmood, Kutub; Dhere, Rajeev; Chen, Dexiang
Highlights: Multiple excipients were screened for their ability to stabilize influenza vaccine. Identified a liquid formulation with storage stability for one year at 2–8 °C. A stable liquid formulation may lead to wider use of influenza vaccination. Abstract: Vaccination is the most effective means of preventing influenza. However, the cost of producing annual seasonal influenza vaccines puts them out of reach for most developing countries. While live attenuated influenza vaccines are among the most efficacious and can be manufactured at low cost, they may require lyophilization to be stable enough for developing-country use, which adds a significant cost burden. The development of a liquid live attenuated seasonal influenza vaccine that is stable for around a year—the duration of an annual influenza season—would significantly improve not only the production output but also the use and accessibility of influenza vaccines in low-resource settings. In this study, potential stabilizing excipients were screened and optimized using the least stable influenza vaccine strain presently known, H1N1 (A/California/07/2009), as a model. The stability-conferring properties of the lead formulations were also tested with a Type B strain of influenza virus (B/Brisbane/60/2008). Stability was also evaluated with higher titers of influenza virus and exposure to agitation and freeze–thaw stresses to further confirm the stability of the lead formulations. Through this process, we identified a liquid formulation consisting of sucrose phosphate glutamate buffer with 1% arginine and 0.5% recombinant human serum albumin that provided storage stability of one year at 2–8 °C for the influenza A and B strains tested.